Optimization of treatment of irritable bowel syndrome in children - O.B. Hanzii; L.G. Voloshyna; O.M. Вabadzhanian; N.V. Pavlenko; O.V. Drachevska (Zaslavsky O.Yu., 2019)
Background. Factors that trigger several pathophysiological mechanisms may simultaneously be involved in the occurrence of irritable bowel syndrome (IBS). Disorders of the intestinal microbiota play a significant role in the pathogenesis of the disease in children, given the characteristics of the child's body. Changes in the composition of the intestinal microflora may be accompanied by movement disorders and impaired sensory sensitivity of the intestines, which form the basis for the formation of pain, dyspeptic manifestations and stool disorders. The lack of effect from the treatment of IBS may be due to the presence of violations of the intestinal biocenosis in the child; therefore, in accordance with the recommendations of the Rome IV criteria, it is necessary to correct the intestinal microflora. The purpose is to study the effectiveness of synbiotic Optilact® in the treatment of irritable bowel syndrome in children. Materials and methods. Thirty-three children aged 8 to 14 years with irritable bowel syndrome (variant with constipation) were examined. The diagnosis was made on the basis of clinical, paraclinical, laboratory and instrumental studies. The dietary supplement Optilact® was prescribed in order to relieve the main complaints - constipation, flatulence, to reduce pain symptoms and improve the general condition of the patient. The effectiveness of therapy was evaluated on the basis of the clinical dynamics of pain and dyspeptic complaints, reduction of constipation. The dynamics of coprological data was assessed by the end of the course of dietary supplement administration. Results. The findings indicate the feasibility and effectiveness of synbiotic Optilact® in children with irritable bowel syndrome (variant with constipation). The positive dynamics of pain and dyspeptic manifestations, the absence of side effects make it possible to use it in children. Conclusions. The use of the dietary supplement Optilact® in the comprehensive therapy of patients with IBS (variant with constipation) reduces pain and dyspeptic manifestations of the disease, eliminates constipation.